REGULARITY OF PHYSIOLOGICAL CHANGES IN THE FUNCTIONAL STATE OF THE BODY OF WORKERS OF A PLANT FOR THE PRODUCTION OF REINFORCED CONCRETE STRUCTURES - Samigova Nargiz (Western European Studies, 2025)
Unfavorable working conditions determine physiological changes in the body of workers at a plant producing reinforced concrete structures, tension in thermoregulatory processes, and the cardiovascular system, which is determined by the influence of harmful production factors on the functional state of the whole organism during the working day.
Keywords: occupational hygiene; production of reinforced concrete structures; workers